Analisis Kurang Optimalnya Sistem Pompa Hidrolik terhadap Kinerja Hatch Cover di Kapal MV. Emerald Indah dengan Metode USG (Urgency, Seriousness, Growth) - Adiisty Nur Fadilla; Dirhamsyah Dirhamsyah; Elly Kusumawati; Agus Prawoto; Frenki Imanto; Shofa Dai Robbi (Pusat riset dan Inovasi Nasional, 2025)
This study aims to analyze the suboptimal performance of hydraulic pump system on hatch cover performance on MV. Emerald Indah using USG (Urgency, Seriousness, Growth) method and data collection techniques in the form of observation, documents, and interview. The purpose of this study is to determine the causes, effect and efforts in solving the problems discussed. The results of the study indicate that several factors cause the hydraulic pump system to not function optimally , including dirty filters, leak in the hydraulic pump and pipe, and operation that is not in accordance with procedures. The effect of the suboptimal hydraulic pressure which ultimately becomes the main problem that inhibits the hatch cover opening process. To overcome this problem, improvements are needed such as periodic filter cleaning, replacement of leaking components, and increasing crew understanding of operational procedures. This research is expected to provide insight for related parties in improving the performanceof the hydraulic pump system and the efficiency of the loading and unloading process on ships.